2009
DOI: 10.3389/neuro.07.014.2009
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive transcranial magnetic stimulation affects behavior by biasing endogenous cortical oscillations

Abstract: A governing assumption about repetitive transcranial magnetic stimulation (rTMS) has been that it interferes with task-related neuronal activity – in effect, by “injecting noise” into the brain – and thereby disrupts behavior. Recent reports of rTMS-produced behavioral enhancement, however, call this assumption into question. We investigated the neurophysiological effects of rTMS delivered during the delay period of a visual working memory task by simultaneously recording brain activity with electroencephalogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
121
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 65 publications
6
121
3
Order By: Relevance
“…In other words, disproportionately out-of-phase rTMS with respect to the intrinsic oscillatory brain activity seems a plausible mechanism to explain how online rTMS may inject neural noise -or random depolarization of neurons (Harris et al, 2008) in the cognitive process being undertaken, thereby temporarily disrupting task performance. Future combined TMS-EEG studies, which are disclosing complex effects of rTMS on endogenous patterns of network-level oscillations (Hamidi et al, 2009), are required to definitely test this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…In other words, disproportionately out-of-phase rTMS with respect to the intrinsic oscillatory brain activity seems a plausible mechanism to explain how online rTMS may inject neural noise -or random depolarization of neurons (Harris et al, 2008) in the cognitive process being undertaken, thereby temporarily disrupting task performance. Future combined TMS-EEG studies, which are disclosing complex effects of rTMS on endogenous patterns of network-level oscillations (Hamidi et al, 2009), are required to definitely test this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…DLPFC may regulate the signal-tonoise ratio of the parietal cortex to enable increased storage capacity (Edin et al 2009). Prior electrophysiological studies have shown that high-frequency rTMS can entrain endogenous alpha frequency in the stimulated area, which then leads to suppression of distracters and thus enhancement of WM capacity (Sauseng et al 2009;Hamidi et al 2009;Thut and Miniussi 2009;Klimesch et al 2003). Other evidence points to the executive role of DLPFC in suppressing interfering task-irrelevant information (Sandrini et al 2008) and updating goal representations based on context information or task-related demands (Brunoni 2014;Barch et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the transfer of visual word information, potentially modulated by effects of spatial attention, would occur primarily between posterior brain regions of extrastriate cortex. Given the novelty of our approach, we chose to limit our analysis to the α-band, where oscillatory activity has been shown to play a role in similar tasks (83)(84)(85)(86). We chose a commonly used α-frequency bandwidth (8-12 Hz), but we note that other studies suggest a functional distinction between the upper and lower α-bands (87).…”
Section: Methodological Considerationsmentioning
confidence: 99%